2014
DOI: 10.1364/oe.22.016267
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting nanowire single photon detector with on-chip bandpass filter

Abstract: Dark count rate is one of the key parameters limiting the performance of the superconducting nanowire single photon detector (SNSPD). We have designed a multi-layer film bandpass filter that can be integrated onto the SNSPD to suppress the dark counts contributed by the stray light and blackbody radiation of the fiber. The bandpass filter is composed of 16 SiO2/Si bilayers deposited onto the backside of a thermally oxidized Si substrate. The substrate shows an excellent bandpass filter effect and provides a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 23 publications
1
49
0
2
Order By: Relevance
“…In recent years, superconducting nanowire single-photon detectors (SNSPDs) 1,2 have emerged as successful alternatives to traditional InGaAs/InP-based single-photon avalanche photodiodes (SPADs) in the realm of near-infrared single photon detection due to their excellent quantum efficiency, [3][4][5][6] short timing jitter, [6][7][8] ultralow dark count rates, [9][10][11] fast reset time with only several nanoseconds, 6,12,13 and photon number resolving ability. [14][15][16] To date, most of SNSPD systems utilize fiber coupling method because of advantages over free-space coupling, including lower dark count rates, more compact size and robustness to vibration.…”
mentioning
confidence: 99%
“…In recent years, superconducting nanowire single-photon detectors (SNSPDs) 1,2 have emerged as successful alternatives to traditional InGaAs/InP-based single-photon avalanche photodiodes (SPADs) in the realm of near-infrared single photon detection due to their excellent quantum efficiency, [3][4][5][6] short timing jitter, [6][7][8] ultralow dark count rates, [9][10][11] fast reset time with only several nanoseconds, 6,12,13 and photon number resolving ability. [14][15][16] To date, most of SNSPD systems utilize fiber coupling method because of advantages over free-space coupling, including lower dark count rates, more compact size and robustness to vibration.…”
mentioning
confidence: 99%
“…Second, with the development of the SNSPD technology, the detection efficiency can be further improved [34]. Besides, the dark count rate may be effectively reduced to sub-Hertz [18]. Last but not least, with the decoy-state parameters and the basis choice optimized [35], we can expect a faster key rate generation to enable some practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In this field-environment test, we develop a decoy-state MDIQKD system, operated at a clock rate of 75 MHz and with a superconducting nanowire single photon detector (SNSPD) system of more than 40% detection efficiency [18]. Our experimental setup is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the extrinsic DCR could be reduced by using cold optical bending fiber [29]. Furthermore, SSPDs with a dielectric multilayer designed to cut the extrinsic DCR also have been presented [31], [32].…”
Section: Sspd Performance In Practical Systemsmentioning
confidence: 99%